Wastewater treatment from the manufacture of solar lenses (Research, Society and Development, 2021)
This work is a partnership with an ophthalmic products company that generates effluents containing a mixture of three dyes: blue 56, yellow 54 and red 60, all in the anthraquinone class. Dyes in this class are resistant to degradation due to their aromatic structure, which retains color for long periods of time. The treatment of these dyes is extremely important due to their toxicity, and may present carcinogenic and mutagenic behavior. The objective of this work was to oxidize polluting organic compounds using advanced oxidative processes. For this, constant current electrolysis was performed using oxide electrodes as heterogeneous catalysts together with Fenton's reagent (Fe2+ + H2O2). Discoloration and oxidation were monitored by UV-Visible spectrometry, high performance liquid chromatography and total organic carbon. The applied treatment allowed a rapid degradation of the chromophore groups and there was a great influence of the hydrogen peroxide concentration on the speed of this degradation. The results were satisfactory, since the coloration was eliminated and the oxidation products identified do not present toxicity and can be easily treated by traditional methods.